Analisa Hubungan Pola Komunikasi Dan Tingkat Keaktifan Pimpinan Terhadap Loyalitas Anggota Pada Komunitas Fotografi Urban Explore Bekasi (Leadership) - Faqihar Risyan (Jurnal Komunikasi, 2019)
This research aims to know the influence of communication patterns and levels of liveliness a leader against the loyalty member in urbex People community beksi region. This research was categorized in the research survey, with research instrumentin the form of a questionnaire. The research is the study of the population by the number of respondents 108 member of urbex people community Bekasi region. metode of research used in this study is a qualitative method, using the approach of Phenomenology. Results of the study found that: (1) a leader of communication patterns of a positive effect against the loyalty member. (2) the level of positive against the influential leader of the liveliness of the loyalty member. (3) the communication pattern and tiers in the influential leader of the simultaneous activity against the loyalty member. It could be said the number of members was strongly influenced by the patterns of communication and levels of liveliness leader itself. KeyWords : Communication Pattern, level of liveliness, and loyality